The Optimization of Curriculum System for Music Education Professionals in the Inheritance and Transmission of Intangible Cultural Heritage Music - Jiang, Min (Pacific International Journal, 2025)
This study examines the optimization of music education curricula for the preservation and transmission of intangible cultural heritage (ICH) music in China, with a focus on Jiangsu Province’s rich musical traditions. Using XX University as a case study, the research explores how higher education institutions can integrate regional ICH music into formal music education programs. Through a mixed-methods approach, the study analyzes curriculum reforms, extracurricular initiatives, and community partnerships that bridge academic training with cultural preservation. Key findings highlight the effectiveness of localized curriculum design, experiential learning, and policy-driven innovation. Localized curriculum design has proven effective in enhancing students’ cultural literacy and technical proficiency. Experiential learning, including practical training, digital tools, and collaborations with ICH inheritors, fosters deeper student engagement with regional music. Policy-driven innovation ensures institutional support and scalability. The results demonstrate that these educational models not only safeguard traditional music but also cultivate a generation of culturally aware professionals capable of addressing the challenges posed by modernization. This study offers actionable insights for global educators and policymakers who are seeking to harmonize cultural preservation with contemporary pedagogical demands.